Introducing patient‐reported outcome in the acute leukemia quality registries in Sweden. (5th March 2020) - Lennmyr, Emma Bergfelt; Karlsson, Karin; Abrahamsson, Marie; Ebrahim, Fereshte; Lübking, Anna; Höglund, Martin; Juliusson, Gunnar; Hallböök, Heléne
Abstract: Objectives: The use of patient‐reported outcome (PRO) measured outside clinical trials is not well defined. We report the first analysis of the prospective PRO study within the Swedish acute myeloid leukemia (AML) and the acute lymphoblastic leukemia (ALL) registries. Methods: PRO was requested 6 months after diagnosis. The EORTC Quality of life Questionnaire Core 30‐item, the Patient Health Questionnaire‐8 (PHQ‐8), and questions from a Swedish National Cancer Questionnaire were used. Results: An invitation letter was sent to 398 patients; 255 (64%) responded, 60% web‐based, and 40% on paper. The ALL cohort had lower physical, role and social functioning, higher symptom burden, and more financial difficulties compared to the AML cohort. A PHQ‐8 score ≥ 10p, which indicates depression, was reported in 18% of the patients; 33% of these patients reported being prescribed antidepressants. The patients' overall experience of care was satisfying, but more psychological and practical support was desired. There was no difference in survival between patients who reported their PRO and those who did not. Follow‐up at 2 and 4 years is ongoing. Conclusions: PRO collected in a registry‐based setting is feasible, but the selection of time points and questionnaires are delicate in a diverse patient population.